2005
DOI: 10.1160/th04-07-0450
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation: the missing link between ADAMTS-13 deficiency and microvascular thrombosis of thrombotic microangiopathies

Abstract: Endothelial injury is the central factor in the events leading to thrombotic microangiopathy (TMA); however, the mechanisms involved are not fully understood. Here we investigate the role of neutrophils (PMNs) and of complement activation in inducing microvascular damage and loss of thromboresistance in TMA associated with ADAMTS-13 deficiency. PMNs isolated during the acute phase of the disease released excessive amounts of reactive-oxygen species (ROS), N-derived oxidants and proteinases and induced damage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 39 publications
1
71
1
Order By: Relevance
“…For instance, serum from patients with TMA caused C3 and membrane attack complex (MAC) deposition on human microvascular endothelial cells (HMEC)-1 and its cytotoxic effect was abolished by complement inhibition. 12 Additionally, plasma levels of C3a and C5a were significantly elevated in patients during acute TTP as compared with those in remission. 13 Most importantly, complement factor H mutations were identified in 5 out of 6 patients with ticlopidine (anti-platelet drug)-associated TTP with severe deficiency of plasma ADAMTS13 activity.…”
Section: Human Neutrophil Peptides and Complement Factor Bb In Pathogmentioning
confidence: 93%
“…For instance, serum from patients with TMA caused C3 and membrane attack complex (MAC) deposition on human microvascular endothelial cells (HMEC)-1 and its cytotoxic effect was abolished by complement inhibition. 12 Additionally, plasma levels of C3a and C5a were significantly elevated in patients during acute TTP as compared with those in remission. 13 Most importantly, complement factor H mutations were identified in 5 out of 6 patients with ticlopidine (anti-platelet drug)-associated TTP with severe deficiency of plasma ADAMTS13 activity.…”
Section: Human Neutrophil Peptides and Complement Factor Bb In Pathogmentioning
confidence: 93%
“…Previous studies have suggested that complement is activated during acute episodes of TTP with reduced levels of serum C3 or elevated platelet-bound C3 (16,(36)(37)(38), with the reservation that older studies did not apply ADAMTS13 diagnostics. A more recent study demonstrated high levels of C3a and sC5b-9 during the acute phase of TTP, normalizing at remission (15), although this study did not find a parallel decrease in serum C3.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when ADAMTS13 is deficient and larger platelet thrombi are allowed to form on damaged endothelium, complement deposition could occur on these cells. TTP sera allowed C3 and C5b-9 deposition to occur on microvascular endothelial cells and upregulated P selectin on the cells thus enhancing the cells capacity to bind neutrophils (16). TTP sera also increased neutrophil degranulation inducing a damaging effect on the cells (16), effects that were attributed to complement activation (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations